2018
DOI: 10.1080/14767058.2018.1437411
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in subsequent pregnancies after wedge resection for interstitial ectopic pregnancy: a retrospective cohort study

Abstract: Findings suggest that a history of WRIEP is not associated with increased risk of adverse pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…This discrepancy may be related to differences in study design, as the Scottish study used women who never had a second pregnancy as the comparison group, rather than all women at their first pregnancy regardless of final parity. In another study, researchers found no increased risk of preterm birth in women with a prior interstitial ectopic pregnancy (8). Interstitial ectopic pregnancy is caused by an embryo that implants in the myometrium near where the fallopian tube connects to the uterus (8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy may be related to differences in study design, as the Scottish study used women who never had a second pregnancy as the comparison group, rather than all women at their first pregnancy regardless of final parity. In another study, researchers found no increased risk of preterm birth in women with a prior interstitial ectopic pregnancy (8). Interstitial ectopic pregnancy is caused by an embryo that implants in the myometrium near where the fallopian tube connects to the uterus (8).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the future birth outcomes of women with ectopic pregnancies. To our knowledge, only two prior studies examined associations between a history of ectopic pregnancy and adverse birth outcomes during a later pregnancy (7,8). An analysis of Scottish national data found that women with an ectopic first pregnancy who had an intrauterine second pregnancy had higher risks of preeclampsia, preterm delivery, and emergency cesarean delivery compared with unexposed women at their second intrauterine pregnancy (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liao et al reported an incidence of subsequent uterine rupture and dehiscence after wedge resection of 30% [32]. This is considerably higher than the uterine rupture rates post myomectomies, which typically range from 0.49 to 0.70% in subsequent pregnancies [32] However, an alternate study has not shown increased risk of uterine rupture in subsequent pregnancy although, in this cohort, the caesarean rate was 60% versus 30% of patients without a history of ectopic pregnancy (P = 0.137) [33].…”
Section: Surgical Managementmentioning
confidence: 62%
“…2,4,5 With regard to the risk of uterine rupture in subsequent pregnancies, we humbly suggest that the authors may have fallen into the trap of selective reporting. Firstly, there is a paucity of long-term data on pregnancy outcomes following interstitial pregnancy, particularly on mode of delivery, and the few authors that have followed up subsequent pregnancies after cornuectomy have not documented any increases in complication rates, 2,[6][7][8] in particular uterine rupture. In any case, many clinicians would recommend an elective caesarean delivery as a full thickness myometrial incision would have been affected, not dissimilar to that following a myomectomy where the uterine cavity had been breached.…”
Section: Dear Editormentioning
confidence: 99%